Rare diseases in disabled children: an epidemiological survey. Issue 2 (17th October 2007) - Guillem, P; Cans, C; Robert-Gnansia, E; Aymé, S; Jouk, P S
Abstract : Aim: To estimate the contribution of rare diseases (RD) to severe impairment in 7-year-old children. Methods: Data from a morbidity register of childhood impairments in a single French region were used. Impairments were classified as a mental, sensorial, neuromuscular (skeletal or movement-related) impairment (MSN_I) according to the International Classification of Functioning. Details of children born from 1980 to 1994 and resident in the county under study when they were 7 years old were recorded. A rare disease was defined as a prevalence rate of <1 per 2000 general population. Results: 26% of children with severe MSN_I had a rare disease; in 36% the MSN_I was of unknown origin. The proportion of impairments that were due to a rare disease varied according to the type of impairment: 3.3% for severe psychiatric disorders; 16.0% for intellectual impairment; 37.2% for hearing impairment; 41.2% for neuromuscular, skeletal and movement impairment; and 81.1% for visual impairment. The overall prevalence rate of rare diseases was 2.1 per 1000 (459/218 283), and it increased significantly over time (p = 0.003). The latter increase was not associated with a decrease in the proportion of impairments of unknown origin, indicating an improvement in the survival of the children with a rare disease. Conclusions: In this study, a rare disease was at the origin of 26% of cases of severe MSN_I. This proportion remained stable over time, whereas the prevalence rate, as well as the prevalence rate of MSN_I disability, increased over time.